WEIGHT LOSS COMPARISON AFTER SLEEVE AND ROUX-EN-Y GASTRIC BYPASS: SYSTEMATIC REVIEW - BARROS,Fernando de (2019)
ABSTRACT Introduction: Bariatric surgery is currently the gold standard treatment for obesity. The two most accomplished surgeries are the Roux-en-Y gastric bypass and the sleeve gastrectomy, and controversies exist in which is better. Objective: To compare the two techniques in relation to weight loss with at least five years of follow-up. Methods: Search in Medline, PubMed, Embase, SciElo, Lilacs, Cochrane databases from 2001 (beginning of vertical gastrectomy) until 2018, using the following headings: “sleeve” or “sleeve gastrectomy” combined with “gastric bypass” or “Roux-en-Y gastric bypass”, “weight loss” and “clinical trial”. Criteria for inclusion of articles were patients aged between 18 and 65 years; clinical trial; comparison between the two techniques; minimum five-year follow-up; outcome with weight loss assessment. Results: The initial search identified 1940 articles, of which 185 publications were identified as clinical trials. One hundred and forty-one were excluded, 67 because they did not compare the two techniques, 57 not addressed weight loss and 17 were repeated articles. Thirty-four studies were retrieved for a more detailed analysis; 36 studies were excluded due to a follow-up of less than five years, and another compared the mini-gastric bypass. In total, seven studies were included in the systematic review, but there was no significant difference in three of them. Conclusion: The gastric bypass had a greater weight loss than the vertical gastrectomy in all the evaluated studies.